Exciton-driven change of phonon modes causes strong temperature dependent bandgap shift in nanoclusters - Franziska Muckel (Nature Portfolio, 2020)
The bandgap of nanostructures usually follows the bulk value upon temperature change. Here, the authors find that in small nanocrystals a weakening of the bonds due to optical excitation causes a pronounced phonon shift, leading to a drastic enhancement of the bandgap’s temperature dependence.